Management of a mandibular first molar with three canals in the distal root - Kesavan, Mohan; Ben Hmida, Sarra Abdulhamid Abdalla; Alshehadat, Saaid Ayesh; Halim, Mohamad Syahrizal; Ahmed, Hany Mohamed Aly (Medknow Publications, 2016)
Adequate knowledge on the root canal morphology is essential for successful root canal treatment. Mandibular molar teeth show considerable variations in their external and internal radicular morphology that require special attention from dental practitioners to provide the best clinical outcomes for the patients. The occurrence of three separate root canals in the distal root of a mandibular molar is uncommon. This article aims to present the endodontic management of a mandibular first molar that has five separate root canals (two root canals in the mesial roots and three root canals in the distal roots).